2020
DOI: 10.1002/jbt.22614
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and silymarin afford protection in cyclosporine A induced hepatorenal toxicity in rat by modulating redox status and inflammation

Abstract: The use of cyclosporine A (CsA) as an immunosuppressive agent is often limited owing to its hepatotoxic and nephrotoxic properties. The present study was designed to evaluate the protective effect of metformin and silymarin in a rat model of CsA induced hepatorenal toxicity. The study included seven groups of Wistar albino rats (n = 6 per group): normal control, experimental control (CsA alone, 25 mg/kg), CsA + metformin (50 and 500 mg/kg), CsA + silymarin (50 and 200 mg/kg) and CsA + vitamin E (100 mg/kg). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…Likewise, the in vitro evidence has also reported that CsA increases the production of ROS in human renal mesangial cells (El‐Sheikh et al., 2019; Wu et al., 2018). The exaggerated overshooting of free radicals and ROS has been characterized to trigger lipid peroxidation of the renal cell membranes resulting in membrane derangements/dysfunction, as proved herein, and in previous reports (Ateyya, 2015; El‐Sheikh et al., 2019; Vangaveti et al., 2021). In the same regard, CsA has been reported to deplete the renal enzymatic/non‐enzymatic antioxidant armory, as seen herein, where CsA diminished the GSH, GPx, and SOD; observations that are in line with several reports (Ateyya, 2015; El‐Sheikh et al., 2019; Wu et al., 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Likewise, the in vitro evidence has also reported that CsA increases the production of ROS in human renal mesangial cells (El‐Sheikh et al., 2019; Wu et al., 2018). The exaggerated overshooting of free radicals and ROS has been characterized to trigger lipid peroxidation of the renal cell membranes resulting in membrane derangements/dysfunction, as proved herein, and in previous reports (Ateyya, 2015; El‐Sheikh et al., 2019; Vangaveti et al., 2021). In the same regard, CsA has been reported to deplete the renal enzymatic/non‐enzymatic antioxidant armory, as seen herein, where CsA diminished the GSH, GPx, and SOD; observations that are in line with several reports (Ateyya, 2015; El‐Sheikh et al., 2019; Wu et al., 2018).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, the depletion of GSH has been reported to disrupt the activity of GPx and sensitize the renal cells to diverse stresses, which contributes to the aggravation of renal oxidative stress (Arab et al., 2018b). Of note, the observed upregulation of NOX‐1 has been reported to mediate the renal injury in several toxicant‐induced renal pathologies (Arab et al., 2018a,b; El‐Naga, 2014; Vangaveti et al., 2021). In the current set of experiments, CsA triggered an upregulated expression of Nrf2 and its downstream HO‐1 target.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Significant protection of oxidative stress (increased SOD activity and GSH levels), inflammation (decreased MPO and TNF-α) is observed in kidney tissues of rat following metformin treatment. Normalization of histological changes, as well as COX-2 and iNOS immunoreactivity scores, further strengthens these findings (Vangaveti et al, 2020).…”
Section: Kidney Diseasessupporting
confidence: 72%
“…Another study showed that MET could reduce the release of mitochondrial ROS and IL-6 in alveolar macrophages exposed to particulate matter of diameter ≤ 2.5 µm (PM2.5) [ 49 ]. The latest research suggests that MET and silymarin have a protective effect upon cyclosporine A-induced hepatorenal toxicity because they restore oxidative homeostasis and regulate the release of proinflammatory mediators [ 50 ]. Those findings provide a theoretical basis for MET in COPD treatment.…”
Section: Introductionmentioning
confidence: 99%